1997
DOI: 10.1046/j.1570-7458.1997.00200.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of parasitism by an encyrtid parasitoid, Anagyrus pseudococci on the survival, reproduction and physiological changes of the mealybug, Planococcus citri

Abstract: Survival, reproduction and some biochemical changes in the citrus mealybug, Planococcus citri (Risso) parasitized by the endoparasitoid, Anagyrus pseudococci (Girault) are reported. The parasitized younger mealybugs were more likely to die than be successfully parasitized. The mean duration (±SE) required for mortality other than mummification were 1.85 ± 0.06, 2.48 ± 0.14 and 2.89 ± 0.17 days for first, second and third instar P. citri respectively. Hosts parasitized in the first instar did not produce any mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 18 publications
1
11
0
3
Order By: Relevance
“…Our findings are supported by [17] who reported the reduction in fecundity of P. citri parasitized by Anagyrus pseudococci, an encyrtid parasitoid which attacks all mealybug instars with preference for the third instar and adult female [17]. Parasitization induces cessation of fecundity of P. citri and the number of eggs produced by parasitized pre-ovopositing and reproductive mealybug adults were significantly different as compared to number of eggs produced by unparasitized adult females [17]. It was also revealed that the percentage of parasitoid's emergence from the mummies of parasitized hosts was different in different host stages.…”
Section: Discussionsupporting
confidence: 86%
“…Our findings are supported by [17] who reported the reduction in fecundity of P. citri parasitized by Anagyrus pseudococci, an encyrtid parasitoid which attacks all mealybug instars with preference for the third instar and adult female [17]. Parasitization induces cessation of fecundity of P. citri and the number of eggs produced by parasitized pre-ovopositing and reproductive mealybug adults were significantly different as compared to number of eggs produced by unparasitized adult females [17]. It was also revealed that the percentage of parasitoid's emergence from the mummies of parasitized hosts was different in different host stages.…”
Section: Discussionsupporting
confidence: 86%
“… K. M. Daane, unpublished data; Islam, Perera & Copland (1997); Walton (2003); Daane et al . (2003).…”
Section: Model Overviewmentioning
confidence: 98%
“…Conocida comúnmente con el nombre de cochinilla harinosa (Granara de Willink y Claps 2003) o cochinilla de los cítricos (Bartlett 1978), se considera una plaga de especial importancia para la agricultura debido a que se alimenta principalmente de plantas cultivadas (Ramos Portilla y Serda Cardona 2004) y algunos otros cultivos hortícolas y ornamentales (Islam et al 1997). Este insecto ataca principalmente las partes aéreas de la planta, los tallos, los botones florales y los frutos jóvenes.…”
Section: Introductionunclassified
“…Aunque se han probado otros agentes de control en P. citri, el parasitoide Anagyrus kamali Moursi (Hymenoptera: Encyrtidae) no es capaz de completar su desarrollo en esta especie (Sagarra et al 2001), así mismo, A. pseudococci (Girault) ha resultado ineficiente como agente de biocontrol, debido a que la mortalidad aparentemente causada por esta especie en las primeras etapas de desarrollo de P. citri, se ha debido a causas ajenas al parasitismo (Islam et al 1997). Otro enemigo natural de la cochinilla de los cítricos comúnmente utilizado es el parasitoide Leptomastix dactylopii (Howard) (Hymenoptera: Encyrtidae) cuyas hembras solamente atacan el tercer y el cuarto instares de este insecto (Lloyd 1958, de Jong y van Alphen 1989.…”
Section: Introductionunclassified